The Effect of Job Insecurity and Job Stress on Turnover Intention with Job Satisfaction as a Mediation Variable - Sari, Okta Puspa; Zunaidah, Zunaidah; Andriana, Isni (Green Publisher Indonesia, 2023)
Study this aim for knowing the influence of job insecurity and job stress on the turnover intention with job satisfaction as variable mediation employee at PT. Graha Maju Property Palembang. Study this done with use approach quantitative with sample 130 employee at PT. Graha Maju Property Palembang. Data processing using Structural Equation Modeling (SEM) with the Smart PLS program. Research results show that job insecurity and job stress are influential and significant to turnover intention. Job satisfaction has a significant effect on turnover intention and can partially mediate the relationship between job insecurity and job stress among employees at PT. Graha Maju Property Palembang.